Characterization and Biocompatibility of Chitosan Gels with Silver and Gold Nanoparticles. (15th September 2014) - Sámano-Valencia, C.; Martínez-Castañón, G. A.; Martínez-Gutiérrez, F.; Ruiz, F.; Toro-Vázquez, J. F.; Morales-Rueda, J. A.; Espinosa-Cristóbal, L. F.; Zavala Alonso, N. V.; Niño Martínez, N.
Abstract : The presence of bacterial resistance to antibiotics is a very important issue and the search of new alternatives is necessary. In this work, a combination of chitosan gel with silver or gold nanoparticles was prepared and characterized using thermal, rheology, bactericide, and biocompatibility analyses. ESEM images were also taken to visualize the incorporation of the nanoparticles into the gel matrix. Thermal analysis showed a better thermal stability in the chitosan-gold nanoparticles gels compared to the chitosan-silver nanoparticles gels. Rheology analyses showed that the viscosity of the gels decreased when velocity increased and there were differences in viscosity when silver and gold nanoparticles concentrations change. ESEM images showed the presence of agglomerates of silver and gold nanoparticles into the gel matrix with a good distribution; in some cases the formation of microstructures was found. Bactericide results show that these materials present an antibacterial activity against S. aureus, S. mutans, and E. coli . The biocompatibility test showed neither negative reaction nor wound healing delay after the application of the gels in an in vivo test. The gels with silver and gold nanoparticles could be used to treat wound infections in oral or skin applications.